Pediatric Trauma Informed Care - Savage, Madeline Carly (My University, 2025)
This integrative literature review aims to research the purpose of pediatric trauma-informed care and how it can help patients in their present and future. Through this integrative literature review, I researched the importance of trauma-informed care(TIC), what TIC is, and how it can be applied in the healthcare system. This literature review's research questions and aims include: How can implementing pediatric trauma-informed care create a better future/outcome for patients? Why is pediatric trauma-informed care important? What are the lasting impacts of pediatric trauma-informed care? How can we implement pediatric trauma-informed care? What is pediatric trauma-informed care?
Keywords: pediatric; trauma-informed care